2012
DOI: 10.3855/jidc.1827
|View full text |Cite
|
Sign up to set email alerts
|

Microbiological and clinical characteristics of diabetic foot infections in northern India

Abstract: Introduction: India has the largest diabetic population of 50.8 million that could reach an epidemic proportion by 2030. Diabetic foot infection is one of the dreaded complications of diabetes. Only a few studies that focus on patterns of diabetic foot infection in our region, where diabetic foot care is inadequate, are available. This study evaluated microbial and clinical characteristics of diabetic foot infections that will be helpful in taking appropriate measures for their management. Methodology: In this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
46
0
4

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 75 publications
(65 citation statements)
references
References 21 publications
13
46
0
4
Order By: Relevance
“…Earlier studies have shown that most diabetic foot infections are polymicrobial with a predominance of Gram-positive cocci especially S. aureus , and Streptococci (Sapico et al, 1984; Jones et al, 1985). However, recent studies indicate the dominance of Gram-negative pathogens in the monomicrobial state, particularly members of family Enterobacteriace and Pseudomonas (Tiwari et al, 2011; Turhan et al, 2013). The prolonged course of antimicrobials for uninfected lesion or healed wounds, long hospital stay, and surgical measures may predispose patients to colonization and infection with drug-resistant pathogens and associated adverse outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…Earlier studies have shown that most diabetic foot infections are polymicrobial with a predominance of Gram-positive cocci especially S. aureus , and Streptococci (Sapico et al, 1984; Jones et al, 1985). However, recent studies indicate the dominance of Gram-negative pathogens in the monomicrobial state, particularly members of family Enterobacteriace and Pseudomonas (Tiwari et al, 2011; Turhan et al, 2013). The prolonged course of antimicrobials for uninfected lesion or healed wounds, long hospital stay, and surgical measures may predispose patients to colonization and infection with drug-resistant pathogens and associated adverse outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…33,39,40,42 In contrast, some other studies have also reported a higher prevalence of mono-microbial infection in diabetic foot. 43,47 In one study, 44 it was noticed that S. aureus and Pseudomonas aeruginosa were the most common causes of diabetic foot infections. In a North Indian study of DFUs, it was found that gram-negative aerobes were the most frequently isolated (51.4%), followed by grampositive aerobes and anaerobes.…”
Section: Microbiology Of Diabetic Foot Infectionmentioning
confidence: 99%
“…33 Fincke et al found large variations in the antibiotic regimens used to treat patients with diabetic foot infections. 47 47 …”
Section: Antibiotic Selectionmentioning
confidence: 99%
“…An additional study conducted by Tiwari and colleagues on 62 DFUs found Escherichia coli to be the most common isolated species followed by Staphylococcus aureus . Microbiological specimens were obtained from tissue biopsies and cultured under aerobic conditions.…”
Section: Introductionmentioning
confidence: 99%